EPCO-06. THE IMPACT OF MISMATCH REPAIR DEFICIENCY (MMRD) ON SURVIVAL OF TEMOZOLOMIDE (TMZ)-TREATED PATIENTS WITH MGMT METHYLATED (M-MGMT) GLIOBLASTOMA (GBM): A CELLWORKS COMPUTATIONAL BIOSIMULATION PILOT STUDY. (14th November 2022) - Castro, Michael; Iwamoto, Fabio; Ahluwalia, Manmeet; Usmani, Shahabuddin; Kumar, Ansu; Kapoor, Shweta; Suseela, Rakhi Purushothaman; Kulkarni, Shruthi; Mohanty, Jharana; Shyamasundar, Vijayashree; Ghosh, Adity; Prasad, Nagendra; et al.
Abstract: BACKGROUND: TMZ-induced G:T mismatches trigger MMR to perform futile repair of O 6 -methylguanine leading to apoptosis. Without MMR, the G:T mutation is genomically incorporated to produce DNA mutation signature #11. Hypermutation ensues and may compromise survival without the redemptive benefit of immunotherapy. MMR genes are infrequently mutated or deleted. More commonly, MMRD results from epigenetic silencing, transcription failure, or micro-RNA compromising translation. METHODS: Comprehensive genomic profiling and Cellworks biosimulation was utilized to diagnose MMRD and correlated with survival in 38 TCGA patients with newly diagnosed, IDH wildtype, m -MGMT GBM treated with adjuvant TMZ. The signaling pathway consequences for MutSα and MutLα were assessed. Kaplan-Meier curves were constructed for PFS and OS. RESULTS: Patients were characterized: MMR proficient (Grp 1) and deficient (Grp 2). Half (19/38) had compromise of 1-10 pathways impacting MMR: 3 had deletions of MLH1 or PMS2 . Others included deletions of EP300, CREBBP, KMT2A-D, ARID1A, HUS, or EXO1 and amplifications of KDM4A/C or MIR21/155 . Grp 1 had significantly higher MMR biosimulation scores than Grp 2. (p=0.00082). The median PFS was 10.51 and 3.58 months (p=0.0072) and median OS was 16.96 and 9.40 (p=0.0059) months in Group 1&2, respectively. CONCLUSIONS: Up to half of GBM patients have MMRD caused by pathway dysregulation. Biosimulation of MMRD predicts early progression on TMZ, echoing the long-held observation that TMZ does not trigger apoptosis in MMRD cancers. The study also reports inferior OS for MMRD compared to the historical experience of unmethylated-MGMT patients, suggesting that TMZ-induced hypermutation may compromise survival. As lomustine does not rely on intact MMR, 2 nd -line lomustine may have blunted the impact of MMR on OS. Alternatively, upfront lomustine might have produced superior disease control in MMRD patients. Computational biosimulation offers the opportunity to diagnose patients who should not receive TMZ despite m-MGMT and who could benefit from alternative adjuvant strategies.